The Impact of Changes in Labor Force Structure on Inequality and Poverty in Indonesia - Bronson Marpaung; Aulia Keiko Hubbansyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Indonesia has demonstrated high and sustained economic growth and has transformed into an industrial and service-oriented nation. The shift of labor from the agricultural sector to non-agricultural sectors such as industry and services has become the center of economic activity. This change can be observed from the increasing contribution of non-agricultural sectors to the economy, accompanied by a decline in the contribution of agriculture in Indonesia. This study differs from others that mainly focus on structural change and its impact on poverty and sectoral inequality, by highlighting the achievement of the turning point condition. Labor surplus in the agricultural sector causes the marginal productivity of labor in this sector to become very low or even nonexistent, a phenomenon that Lewis referred to as disguised unemployment, which frequently occurs in the agricultural sector of developing countries. The aim of this study is to identify the Lewis Turning Point (LTP) and analyze the impact of changes in labor structure on inequality and poverty in Indonesia. This study utilizes secondary data from several institutions, including the World Bank, Food and Agriculture Organization (FAO), and UNCTAD, in the form of time series data for the period 1980-2020. In this study, Indonesia has not yet reached the Lewis turning point as a result of the structural change process. The transformation from the agricultural sector to the industrial sector can reduce poverty and inequality, while the transformation from the agricultural sector to the service sector has proven unable to reduce inequality and poverty.